CONSTRUCTIVISM GOES QUANTUM: THE APPROACH REFORM - T. A. Alekseeva; A. P. Mineev; A. V. Fenenko; I. D. Loshkariov; B. I. Ananyev (Vestnik MGIMO-Universiteta)
The article deals with the evolution of constructivist paradigm of international relations. The issue is of utmost importance in terms of the search for theoretical alternatives in the IR thinking. First, we are giving basic introduction of constructivism on the basis of historical and hermeneutical approaches. There is no doubt that the paradigm has faced different theoretical challenges and a lot of critics which has to be addressed. The authors reconsider some constructivist theories and notions in Alexander Wendt's works and the way Wendt tried to reinforce and reassure the constructivist paradigm. This allows us to claim that quantum turn in recent Wendt's work was almost inevitable. Second, the article attempts to answer a question whether the fundamentals of quantum physics are relevant when speaking about social and political processes. At first glance, quantum physics approach has nothing in common with the theory of politics and the theory of international relations. However, there are some grounds to believe that certain problem issues of the political science and IR theory are not deadlocks. In the second part of the article we use the unleashed and underestimated potential of analytical philosophy. To conclude, we believe that today there are more questions than answers but the quantum paradigm is expected to be the important part of the political studies and IR theory as well.